Impact of SWCNT-conjugated senna leaf extract on breast cancer cells: A potential apoptotic therapeutic strategy - Behairy Sabreen Mohammed; Al-Maaqar Saleh Mohammed; Al-Shaeri Majed Ahmed (Open Life Sciences)
Breast cancer (BC) has a prevalence rate of 21.8% among Saudi women and ranks as the third leading cause of death in Western nations. Nanotechnology offers innovative methods for targeted BC therapy, and this study explores the use of single-walled carbon nanotubes (SWCNTs) for delivering the senna leaf extract. The study evaluated the effects of increasing dosages of senna leaf extract conjugated to SWCNTs on MCF-7 cells. Cell viability was assessed using the MTT assay, while Giemsa staining revealed morphological changes. Additionally, the comet assay and agarose gel electrophoresis were employed to evaluate the pro-apoptotic potential. The potential of mitochondrial membrane and the production of reactive oxygen species (ROS) were investigated using the JC-1 dye. The results indicated that treated cells exhibited apoptotic characteristics, including elevated ROS levels and decreased mitochondrial membrane potential. In summary, the application of nanotechnology to deliver the senna leaf extract shows promise as a herbal treatment for BC, suggesting a potential breakthrough in combating this widespread and deadly disease.